A legal assessment of the International Code for Ships Operating in Polar Waters (the Polar Code) - Braathen, Victoria (UiT Norges arktiske universitet, 2016)
January 1, 2017 the International Code for Ships Operating in Polar Waters (the Polar Code) will enter into force. The Polar Code is the result of enduring efforts by the international community, and is characterized as a “historic milestone” in the work of the IMO to establish a unified system for polar navigation. The purpose of this paper is to submit an assessment of the Polar Code in the context of international law of the sea, preceded by an account of the instrument background and key features. Do provisions of the Polar Code qualify as “generally accepted international rules and standards”, and the relation between the Polar Code and the extended environmental jurisdiction granted Arctic coastal states, are among key issues to be addressed.